Intrahepatic diffuse periportal enhancement patterns on hepatobiliary phase gadoxetate disodium-enhanced liver MR images: Do they correspond to periportal hyperintense patterns on T2-weighted images?. Issue 11 (March 2019) - Onishi, Hiromitsu; Theisen, Daniel; Zachoval, Reinhart; Reiser, Maximilian F.; Zech, Christoph J.
Abstract : Abstract: The purpose of this study was to investigate the findings of diffuse periportal enhancement in the liver on hepatobiliary phase gadoxetate disodium-enhanced magnetic resonance images by comparing with the finding of periportal hyperintensity on T2-weighted images and to reveal their clinical significance. Nineteen consecutive patients with diffuse periportal enhancement on hepatobiliary phase images constituted the study population. The intrahepatic diffuse periportal enhancement finding was assessed on whether it corresponded to periportal hyperintense patterns on T2-weighted images or not in the location, and the cases were classified into 2 groups according to this characteristic. Signal intensities at the periportal areas were also assessed on T1-, T2-, diffusion-weighted and dynamic images. Furthermore, possible associations between these image findings and the final diagnoses were explored. In 7 of the 19 patients, periportal enhancement area corresponded with the periportal hyperintensity area on T2-weighted images. In the remaining 12 patients, the finding of periportal T2-hyperintensity was absent or the periportal enhancement differed from the periportal T2-hyperintensity in the location. Diseases of the former group comprised autoimmune hepatitis, acute exacerbation of chronic hepatitis and acute alcoholic steatohepatitis, and those of the latter group primary sclerosing cholangitis, autoimmune hepatitis-primary biliary cirrhosis overlap syndrome, and liver cirrhosis with miscellaneous etiology. Diffuse periportal enhancement during the hepatobiliary phase did not always correspond to periportal hyperintensity on T2-weighted images. In the classification based on whether enhancement area corresponded or not, each enhancement pattern appeared in different groups of liver diseases. Specifically, the former (corresponding) was associated with active inflammation such as hepatitis and the latter (not corresponding) was predominantly associated with a chronic change such as cirrhosis. Appropriate recognition of these periportal enhancement patterns may contribute to the improved diagnosis of diffuse liver diseases.